Los problemas en la medición del grado de cumplimiento de los Objetivos de Desarrollo Sostenible: La inclusión del "impulso en sostenibilidad" - Maria Cendán Castillo (Atlantic Review of Economics (ARoEc), 2021)
– International agendas have included sustainability within the concept of development as the main concern that must be addressed from a global perspective. The proposal of a single index for sustainable development makes it possible to combine the measurement of results and unify criteria. However, the levels of development together with the idiosyncrasy of each country have a direct impact on the degree of compliance with the sustainable development goals proposed by the 2030 Agenda. The purpose of this article is to reflect on the relationship between the starting point of developing countries, through the three components of the Human Development Index, and the degree of compliance with the SDGs reflected in the results of the SDG Index. From a bibliographic review, which is complemented by quantitative analysis, essentially descriptive statistics with a comparative nature, as well as a correlation analysis, we will conclude the need to take into account the indicator "impulse in sustainability".
Keywords: F63; O19; 330; sustainable development; sustainable development goals; synthetic index; Agenda 2030; sustainable effort; Human Development Index